Increasing Creative Competence Of Students And Strengthening Educational Efficiency Based On Individual Approach - Zulfiya Aytbаyevna Jumaniyazova (Euro Asian Journal Publishing, 2024)
On the fundamental principles of forming a competency-based approach in the paradigm of modern education, which allows for the assignment of an important didactic goal to students' independent work.
Keywords: pragma; competence; didactic; creative